Penggunaan User Experience Questionnaire Dan Usability Testing Mengevaluasi Pengalaman Pengguna Aplikasi BNI Mobile Banking - Sahulata, Reynoldus Andrias (Direktorat Riset dan Pengabdian Pada Masyarakat (DRPM) Universitas Bina Darma, 2025)
The development of information technology in the world has experienced very rapid growth, there are many applications that make it easier for us, such as Mobile Banking and BNI 46 is one of the BUMN (State-Owned Enterprises) banks that has a mobile application, namely BNI Mobile Banking. The objective of this study is to analyze the impact and evaluate user experience on the BNI Mobile Banking application based on UEQ and Usability Testing. The results of this research used 65 respondent data for UEQ and Usability Testing using 20 respondent data which had been collected for more than 4 weeks in the city of Manado. Evaluation with UEQ revealed that BNI Mobille Banking users gave positive scores on the scale of Attractiveness, Perspicuity, Efficiency, Dependability, Stimulation and Novelty. For the Usability Testing evaluation, there are 2 scenarios which are calculated using the maze and also get positive values ​​for both scenarios.